(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation: Phonetics is a branch of linguistics that focuses on the study of the sounds used in speech. It is concerned with how these sounds are produced, transmitted, and perceived by humans. Phonetics plays a crucial role in understanding the structure and function of language, as well as in improving communication and language teaching.